FT-IR analysis of acid black dye biodegradation using saccharomyces cerevisiae immobilized with treated sugarcane bagasse - Mitter, E. K.; Corso, C. R. (Springer Nature, 2013)
Textile industries use large amounts of water in dyeing processes and a wide variety of synthetic dyes. A small concentration of these dyes in the environment can generate highly visible pollution and changes in aquatic ecosystems. Adsorption, biosorption, and biodegradation are the most advantageous dye removal processes. Biodegradation occurs when enzymes produced by certain microorganisms are capable of breaking down the dye molecule. To increase the efficiency of these processes, cell immobilization enables the reuse of the immobilized cells and offers a high degree of mechanical strength, allowing metabolic processes to take place under adverse conditions. The aim of the present study was to investigate the use of Saccharomyces cerevisiae immobilized in activated sugarcane bagasse for the degradation of Acid Black 48 dye in aqueous solutions. For such, sugarcane bagasse was treated with polyethyleneimine (PEI). Concentrations of a 1 % S. cerevisiae suspension were evaluated to determine cell immobilization rates. Once immobilization was established, biodegradation assays for 240 h with free and immobilized yeast in PEI-treated sugarcane bagasse were evaluated by Fourier transform infrared spectrophotometry. The results indicated a probable change in the dye molecule and the possible formation of new metabolites. Thus, S. cerevisiae immobilized in sugarcane bagasse is very attractive for biodegradation processes in the treatment of textile effluents. © 2013 Springer Science+Business Media Dordrecht.
Keywords: Acid Black 48; Biodegradation; FT-IR; Immobilization; Saccharomyces cerevisiae; Sugarcane bagasse; Textile dyes; Biodegradation process; Fourier transform infrared spectrophotometry; Immobilization rates; Immobilized yeasts; Small concentration; Sugar-cane bagasse; Bagasse; Cell immobilization; Dyes; Microbiology; Molecules; Radioactive waste vitrification; Textile industry; Yeast; black dye; dye; polyethyleneimine; unclassified drug; biodegradation; effluent; FTIR spectroscopy; immobilization; textile industry; waste treatment; yeast; bioassay; concentration (parameters); controlled study; immobilized cell; industrial waste; infrared spectroscopy; microbial degradation; nonhuman; phytoremediation; plant residue; recycling; sugarcane; waste management; water contamination